The Future of Heterodox Economics: An Institutional Perspective. Issue 3 (3rd July 2021) - Dequech, David
Abstract: This article looks at the future of heterodox economics from an institutional perspective, while commenting on Geoffrey Hodgson's 2019 book on this issue. It contrasts heterodox and mainstream economics, identifies some problems facing the former and discusses what should be done.